Chemistry of Depsides from Manglicolous lichen Dirinaria consimilis (Stirton) D.D. Awasthi along with their Pharmacological Insights - Vinay Bharadwaj Tatipamula; Girija Sastry Vedula (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
This book chapter provides a thorough examination of the isolation process, structural characterization, and pharmacological properties of two novel depsides, Antarvedisides A and B, extracted from Dirinaria consimilis (Stirton) D.D. Awasthi, alongside several known depsides. The study explores the compounds’ structural features and delves into their pharmacological profile, emphasizing their potential as promising candidates for future drug development. Chromatographic examination of acetone extract of D. consimilis yielded Antarvedisides A and B, sekikaic acid, atranorin, divaricatic acid and 2’-O-methyl divaricatic acid. Antioxidant activity assessment through superoxide, DPPH and ABTS radical scavenging assays reveals that Antarvedisides A-B and 2’-O-Methyldivaricatic acid exhibit remarkable antiradical scavenging capacities, surpassing the standard drug, ascorbic acid. The investigation extends to in vitro anti-inflammatory activity, where atranorin exhibits superior inhibition against protein denaturation in comparison to the standard drug indomethacin. Antarvedisides A-B showcases moderate anti-inflammatory activity, further detailed with IC50 values ranging from 878-600 µg/mL. The anticancer potential of the depsides is highlighted through the Sulforhodamine B assay screening. Antarvediside B emerges as a potent inhibitor of cell growth in MCF-7 and HeLa, outperforming doxorubicin. Additionally, 2’-O-methyldivaricatic acid demonstrates significant inhibitory profiles against various cancer cell lines. In conclusion, this abstract summarizes the comprehensive pharmacological profile of Antarvedisides A and B, shedding light on their antioxidant, anti-inflammatory, and anticancer activities. These findings underscore the potential of these depsides as valuable candidates for further drug development and contribute to the expanding knowledge of natural compounds with therapeutic implications.